Developing English Material of Agriculture for 7th Grade Students of SMP Plus Al-Mubarak Kalisat, Jember - Mahmud, Mohammad; Sugiyono, Sugiyono (ELLITE, 2019)
A lot of seventh grade students of SMP Plus Al-Mubarak found many problems in understanding their English instructional materials. Designing English Materials of Agriculture for students in SMP Plus Al-Mubarak Kalisat, Jember can motive them in learning English better. Concerning these problems, a set of suitable instructional materials of English for the students of SMP Plus Al-Mubarak needed to be developed. In addition, instructional materials should facilitate the students to enrich their experience, build their knowledge, and construct their comprehension. The instructional materials should consider where the student’ life, culture, background, interest, and their ability. The procedures being employed in this study were R D (Research and Development); collecting information, developing instructional materials, conducting expert validation, revising the materials, finishing the submitted product. (Adapted from Borg and Gall’s Model, 1983). To collect relevant information for a basis of developing materials, the interview with the teacher and students and classroom observation were carried out to complete the information provided in the existing materials. The product of this research is five units of English materials of agriculture which focuses on second semester.